Effect of Triplet Confinement on Triplet–Triplet Annihilation in Organic Phosphorescent Host–Guest Systems. (12th November 2018) - Ligthart, Arnout; de Vries, Xander; Zhang, Le; Pols, Mike C. W. M.; Bobbert, Peter A.; van Eersel, Harm; Coehoorn, Reinder
Abstract: The efficiency of phosphorescent organic light emitting diodes (OLEDs) shows a decrease with increasing luminance ("roll‐off"). One of the contributions to the roll‐off is triplet–triplet annihilation (TTA). TTA is the process of energy transfer from one triplet exciton to another, after which the excited exciton decays nonradiatively to the lowest triplet state. In this study, the TTA‐rate is measured for a large number of emissive materials consisting of a small concentration of phosphorescent "guest" molecules, with emission colors across the entire visible range, embedded in various host materials. It is found that the TTA‐rate does not only depend on the direct interaction rate between the excitons on the guest molecules, but also on the difference in triplet energy Δ E T of the host and guest molecules: when Δ E T is smaller than about 0.20 eV, diffusion of excitons via the host molecules leads to a significant enhancement of the TTA‐rate. By varying the guest concentration and using kinetic Monte Carlo simulations, the roles of the direct interaction, guest‐mediated diffusion, and host‐mediated diffusion are disentangled. Abstract : The efficiency of phosphorescent organic light emitting diodes (OLEDs) decreases with increasing luminance ("roll‐off"). One of the contributions to the roll‐off is triplet–triplet annihilation (TTA). The TTA‐loss for 22 host–guest systems is measured, and the role of the direct TTA process and of triplet diffusion is disentangled and quantified using a recently proposed analysis method and kinetic Monte Carlo simulations.